Tests of factorial structure and measurement invariance for the Student Engagement Instrument: Evidence from middle and high school students in Portugal - Moreira, Paulo Alexandre Soares (2018)
Corresponding Author: Paulo A. S. Moreira, Pg. D., Instituto de Psicologia e de Ciências da Educacão, Universidade Lusíada—Norte (Porto), Porto, Portugal, Centro de Investigação em Psicologia para o Desenvolvimento, CIPD, Porto, Portugal paulomoreira@por.ulusiada.pt